Indigenous engagement challenges and carbon mitigation activities in Malaysian forest policy - Guglyuvatyy, Evgeny (Frontiers in Forests and Global Change, 2024)
Malaysia’s commitment to achieving net-zero emissions by 2050 hinges on its ability to protect its abundant carbon sinks, notably its natural forests. However, several challenges impede effective forest protection, including the undervaluation of forested land, the absence of regulatory safeguards against land use changes, and the insufficient protection of land rights of indigenous communities. This paper examines these challenges and their implications for Malaysia’s net-zero emissions goal. It argues that remedial action is necessary, including the development of carbon credit mechanisms that recognize indigenous communities as integral stakeholders and the implementation of regulatory reforms to address the undervaluation of forested land and to strengthen the protection of land rights of indigenous communities.